Monte Carlo Simulation of the Backscattering Gamma Ray System - Kadhim, A.; Mohammad, A. (Iraqi Journal of Science, 2023)
A Monte Carlo simulation has been used to design program which simulate gamma rays backscattering system. Gamma ray backscattering is very important to get useful information about shielding, absorption and counting problems. Simulation was done of a 661.6 KeV from a collimated point source of 137Cs. When increasing the scattering angle of photon which emerging from Iron target , as the incident gamma beam angles of 15°, 45° and 75°, the results showed that the single scattering count decreases. Whereas, this count increased by increasing the incident angle. In addition, the single scattering peak (count) increases according to the sample thickness until „saturation thickness‟. Our simulation results are useful to evaluate the optimal configuration of systems using Compton backscattered radiation and to access the feasibility for setting up experimentally this system. Also, it will be used to determine the best conditions under which this method can be applied to testing electron densities or to assess the thickness of sample to locate defects in them.